Regenerative therapies for femoral head necrosis in the past two decades: a systematic review and network meta-analysis - Xiaole Wang; Liyou Hu; Bo Wei; Jian Wang; Decai Hou; Xiaolei Deng (Stem Cell Research & Therapy, 2024)
Abstract Background Regenerative techniques combined with core decompression (CD) are commonly used to treat osteonecrosis of the femoral head (ONFH). However, no consensus exists on regeneration therapy combined with CD that performs optimally. Therefore, we evaluated six regenerative therapies combined with CD treatment using a Bayesian network meta-analysis (NMA). Methods We searched PubMed, Embase, Cochrane Library, and Web of Science databases. Six common regeneration techniques were categorized into the following groups with CD as the control group: (1) autologous bone graft (ABG), (2) autologous bone graft combined with bone marrow aspirate concentrate (ABG + BMAC), (3) bone marrow aspirate concentrate (BMAC), (4) free vascular autologous bone graft (FVBG), (5) expanded mesenchymal stem cells (MSCs), and (6) platelet-rich plasma (PRP). The conversion rate to total hip arthroplasty (THA) and progression rate to femoral head necrosis were compared among the six treatments. Result A total of 17 literature were included in this study. In the NMA, two of the six treatment strategies demonstrated higher response in preventing the progression of ONFH than CD: MSCs (odds ratio [OR]: 0.098, 95% confidence interval [CI]: 0.0087–0.87) and BMAC (OR: 0.27, 95% CI: 0.073–0.73). Additionally, two of the six treatment strategies were effective techniques in preventing the conversion of ONFH to THA: MSCs (OR: 0.062, 95% CI: 0.0038–0.40) and BMAC (OR: 0.32, 95% CI: 0.1–0.074). No significant difference was found among FVBG, PRP, ABG + BMAC, ABG, and CD in preventing ONFH progression and conversion to THA (P > 0.05). Conclusions Our NMA found that MSCs and BMAC were effective in preventing ONFH progression and conversion to THA among the six regenerative therapies. According to the surface under the cumulative ranking value, MSCs ranked first, followed by BMAC. Additionally, based on our NMA results, MSCs and BMAC following CD may be necessary to prevent ONFH progression and conversion to THA. Therefore, these findings provide evidence for the use of regenerative therapy for ONFH.